Pengaruh Latihan Up Hill Dan Fartlek Terhadap Kemampuan Vo2max Atlet SSB - Jamaludin, Jamaludin; Suriatno, Adi; Mujriah, Mujriah (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
VO2max has a very close relationship with the game of soccer because soccer games are played for quite a long time, namely two forty-five minutes, so a player must have good endurance before he can play according to what a coach wants. A soccer player's sporting performance is determined by high muscle endurance and cardiac and pulmonary endurance. Meanwhile, uphill training and fartlek training play a role in maintaining endurance and will help players avoid the risk of Overuse Injury. Many coaches only pay attention to muscle training without taking into account the endurance or VO2max of their players. The aim of this research was to determine the effect of uphill training and fartlek training on the VO2max ability of soccer players aged U13-14. The type of research used was experimental research with a two groob pre test post test design, with a sample size of 25 people who were divided into two groups, 13 people aged 13 years were given uphill training and 12 people aged 14 were given fartlek training. The instrument used to measure VO2max ability is the Bleep Test (multi-stage running). Data analysis used in this research used the t test. The results of this research show that uphill training and fartlek training can increase the VO2max ability of soccer players at SSB Bintang Kejora in students aged 13-14 years.